(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
The objective of this study was to develop a pharmaceutical O/W emulsion containing plant-derived polyphenol extracts and evaluate its stability and antioxidant activity. O/W emulsions were prepared using ionic surfactant polysorbate 80 (Tween 80®). The odorwas adjusted with few drops of blue sea fragrance. DPPH (1,1-diphenyl-2-picrylhydrazyl) assay was used to evaluate the antioxidant activity of the plant extracts alone and emulsions containing these extracts. Physical stability was assessed by submitting the emulsions to storage at 8 ºC, 25 ºC, 40 ºC and 40 ºC + 70% RH (relative humidity) for two months. Various physical characteristics of emulsions monitored, include color, creaming, liquefaction, centrifugation and pH. Brookfield rotational rheometer was used to determined viscosities and rheological behavior of emulsions. Different types of emulsion were determined microscopically, while pH values of emulsions were measured by a pH meter. Electrical conductivity data confirmed that the outer phase was water. Samples presented an acceptable pH value for an external topical use. Shear thinning behaviour was observed for all emulsions. The polyphenol-rich-plant-derived extracts alone and the extract containing emulsions showed good antioxidant activities. This research confirmed that the method used was suitable for preparing emulsions with Hippophae rhamnoids and Cassia fistula extracts, suggesting that those emulsions are suitable for topical use.